Megatrends and Structural Change — Which Regions Will Benefit? - Mirko Kruse; Dörte Nitt-Drießelmann; Jan Wedemeier (Wirtschaftsdienst)
Abstract Structural change and transformation is not a temporary phenomenon. The regional economic structure decides whether or not structural change has a positive effect on a region. In Germany, the process of structural change encounters heterogeneous regions that differ in terms of e.g. spatial structure, demography or economic strength. Moreover, urban areas can adapt particularly well to current trends, while rural and peripheral areas threaten to fall behind. The article presents the findings of a model that assesses how well regional economic structures in Germany are adapted to upcoming megatrends as well as market and technology trends. The model assesses both future development potential and past development. It concludes that changes should not be halted by structure conserving policies but should rather be taken up proactively in order to shape change. This requires an innovation policy that is increasingly aimed at cooperation and networking.